1977
DOI: 10.1161/01.cir.55.3.537
|View full text |Cite
|
Sign up to set email alerts
|

The effect of jejunoileal bypass on the pharmacokinetics of digoxin in man.

Abstract: Seven subjects who underwent jejunoileal bypass surgery for massive obesity participated in a study to examine the relative bioavailability of digoxin before and one to two months after surgery. They were given a loading dose of 1 mg digoxin in divided oral doses followed by oral maintenance doses of 0.5 mg daily. There were no significant differences in the area under the serum concentration time curve, steady state serum levels or 24 hour steady state excretion of digoxin before and after surgery. We conclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, a strong correlation was found between AUe or peak serum digoxin concentrations and the length of the remaining jenunum. These results were not sustained by Marcus et al (1977) or Krausz et al (1979), who did not find any significant differences in digoxin absorption before and after small bowel resections. Heizer et al (1971) found a slightly reduced digoxin absorption in a patient with jejunocolostomy and in patients with idiopathic malabsorption, while the absorption was normal in patients with gastrectomy even when the duodenal mucosa was bypassed as in the Billroth II operation (Beermann et aI., 1973).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, a strong correlation was found between AUe or peak serum digoxin concentrations and the length of the remaining jenunum. These results were not sustained by Marcus et al (1977) or Krausz et al (1979), who did not find any significant differences in digoxin absorption before and after small bowel resections. Heizer et al (1971) found a slightly reduced digoxin absorption in a patient with jejunocolostomy and in patients with idiopathic malabsorption, while the absorption was normal in patients with gastrectomy even when the duodenal mucosa was bypassed as in the Billroth II operation (Beermann et aI., 1973).…”
Section: Discussionmentioning
confidence: 73%
“…Drug kinetics might thus be affected by the shunt operation in several ways: exclusion ofa section of varying length of the small intestine might affect drug absorption; the weight loss will change drug distribution; and metabolism could be decreased by postoperatively induced hepatic disease. However, pharmacokinetic studies in intestinal bypass patients dealing with antiepileptic drugs (Kennedy and Wade, 1979;Peterson and Zweig, 1974), anti- pyrine (Andreasen et a!., 1977), digoxin (Gerson et a!., 1980;Marcus et a!., 1977) and antituberculous drugs (Bruce and Wise, 1977;Polk et aL, 1978;Wasson and Harris, 1976) have produced conflicting results, which might be partly explained by differences in the experimental design. The most frequently used procedure -comparison of an operated and a normal control group -introduces a great interindividual error, and drug administration by the oral-route only makes it impossible to estimate the absolute bioavailability of the agents involved.…”
mentioning
confidence: 99%
“…Krausz et al (1979) found that digoxin absorption was not impaired in a patient with complete small bowel resection except for the proximal 15cm of the jejunum. Furthermore, Marcus et al (1977) found no differences in digoxin absorption in 7 patients before and after jejunoileal bypass. Thus, these surgical interventions have little if any effect on the extent of digoxin absorption.…”
Section: Effect Of Surgically-induced Gastrointestinal Abnormalities mentioning
confidence: 77%
“…Likewise, that of phenytoin was significantly lowered (Kennedy & Wade, 1979). This was not the case for digoxin (Marcus et al, 1977), phenazone (Andreasen et al, 1977), ampicillin and propylthiouracyl (Klein et al, 1977).…”
Section: Discussionmentioning
confidence: 99%